PENGAKUAN TANPA SUKARELA SERTA KESANNYA DALAM UNDANG-UNDANG KETERANGAN ISLAM - Mohamad, Mohd Nasran (Jurnal Syariah, 2019)
The central concern of this anicle is to view how far an accused person's decision to confess his guilt in the Coun of justice is in free will and without any undue influence or duress and knows the consequence of his confessions. The discussion will emphasis the rights of the accused in Islamic coun and other related issues.